2023
DOI: 10.1002/mc.23585
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 induces non‐small cell lung cancer metastasis via GCN5‐dependent SOX4 acetylation enhancing MMP9 gene transcription and expression

Abstract: Interleukin‐17 (IL‐17), a potent proinflammatory cytokine, can trigger the metastasis of non‐small cell lung cancer (NSCLC). However, the underlying mechanism involved in IL‐17‐induced NSCLC cell metastasis remains unclear. In this study, we found that not only the expression of IL‐17, IL‐17RA, and/or general control nonrepressed protein 5 (GCN5), SRY‐related HMG‐BOX gene 4 (SOX4), and matrix metalloproteinase 9 (MMP9) was increased in the NSCLC tissues and in the IL‐17‐stimulated NSCLC cells, but also IL‐17 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The MMP9 has been extensively studied and its close association with proliferation, migration, and invasion has been well‐documented, primarily implicated in the metastasis of NSCLC. 77 , 78 , 79 In microvasculitis, the entry of monocytes and T cells into the blood vessel wall is elegantly regulated by MMP9. T cells rely on MMP9‐producing monocytes to gracefully traverse the basement membrane containing collagen‐IV.…”
Section: Discussionmentioning
confidence: 99%
“…The MMP9 has been extensively studied and its close association with proliferation, migration, and invasion has been well‐documented, primarily implicated in the metastasis of NSCLC. 77 , 78 , 79 In microvasculitis, the entry of monocytes and T cells into the blood vessel wall is elegantly regulated by MMP9. T cells rely on MMP9‐producing monocytes to gracefully traverse the basement membrane containing collagen‐IV.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments showed that the migration and invasion of cancer cells are mainly related to the up-regulation of the downstream gene MMP9, and in vivo experiments found that the number of metastatic nodules in lung tissues is significantly reduced after interfering with MMP9 expression. Specific mechanism exploration suggested that IL-17 regulation of non-small cell lung cancer metastasis is closely related to the GCN5-SOX4-MMP9 axis[ 46 ]. Metastasis is a major cause of cancer development and death, and the production of neutrophil extracellular traps (NETs) have an influential role in the pathogenesis of the metastatic cascade.…”
Section: Discussionmentioning
confidence: 99%